The Cost Assignment of the Cooperative Water Resource Development: A Game Theoretical Approach - Suzuki, Mitsuo; Nakayama, Mikio (Management Science, 1976)
As the demand for natural resources intensifies so too the costs of further exploitation of these resources become enormous. These enormous costs in turn require the development of a given resource to be a cooperative venture among several participants, each of whom must be assured that the costs and benefits of the venture will be “fairly” distributed among them. It is at this point that the theory of cooperative games may offer guidelines as to what is fair or not fair to each participant or player in a given cost allocation. To illustrate an application of cooperative game theory in assigning “fair” costs and benefits to the participants in a cooperative venture we will consider a problem in water resource development.